Conductivity type conversion in p-CdZnTe under pulsed laser irradiation - Tetyorkin, V.V.; Sukach, A.V.; Krolevec, N.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Laser-induced surface modification is investigated in p-Cd₀.₉Zn₀.₁Te under
irradiation with nanosecond pulses of YAG:Nd laser by using the power density
5 MW/cm². Conductivity type conversion of the near-surface region with the thickness of
several micrometers is observed. The surface-barrier structures were prepared by
electrolytic deposition of Au onto the irradiated surface. The spectral dependences of the
photovoltaic response has been explained by formation of the graded band gap in the
irradiated region. The direct current conductivity has been proved to be determined by
the dislocation network.